Into the wild - Jon Krakauer (Anchor Books, 1996)
In April 1992 a young man from a well-to-do family hitchhiked to Alaska and walked alone into the wilderness north of Mt. McKinley. His name was Christopher Johnson McCandless. He had given $25,000 in savings to charity, abandoned his car and most of his possessions, burned all the cash in his wallet, and invented a new life for himself. Four months later, his decomposed body was found by a moose hunter....
Keywords: Autobiographies / Biographies -- Autobiographies / Biographies